2020
DOI: 10.3390/nu12072104
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Magnesium Intake and Chronic Pain in U.S. Adults

Abstract: Chronic pain is a public health concern and additional treatment options are essential. Inadequate magnesium intake has been associated with chronic pain in some populations. We sought to examine the relationship between dietary magnesium intake and chronic pain in a large, representative cohort of U.S. adults (NHANES). Of the 13,434 eligible adults surveyed between 1999 and 2004, 14.5% reported chronic pain while 66% reported inadequate magnesium intake. The univariate analysis showed a protective effect of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Pain severity was also positively associated with a high fat and sugar intake [125] and a low fruit and fiber intake [126]. There is also evidence that a low intake of magnesium and folic acid contributes to chronic musculoskeletal pain [127], whereas a high magnesium intake confers protective effects [128].…”
Section: Musculoskeletal Painmentioning
confidence: 99%
“…Pain severity was also positively associated with a high fat and sugar intake [125] and a low fruit and fiber intake [126]. There is also evidence that a low intake of magnesium and folic acid contributes to chronic musculoskeletal pain [127], whereas a high magnesium intake confers protective effects [128].…”
Section: Musculoskeletal Painmentioning
confidence: 99%
“…Interestingly, although the intake of vitamin D was not statistically different, total intake of was very low, particularly given the ability of vitamin D to reduce inflammation [ 34 ]. Furthermore, green leafy vegetables are high in magnesium and potassium, where dietary magnesium can help muscle function and may improve MPs [ 35 ]. In line with this study, many previous studies found a strength association between dietary approach to stop hypertension (DASH) diet and improving body composition (reducing body fat and increasing muscle strength) and relieving pain [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a greater intake of sodium can increase pain (Salgado et al., 2015 ). Finally, foods rich in acid‐producing properties are usually low in magnesium; this nutrient can help to eliminate chronic pain due to prolonged opening of calcium channels and activation of N‐methyl‐D‐aspartate (NMDA) receptors, which can remain open in the absence of magnesium (Tarleton et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%